Antecedentes da reciclagem de resíduos eletrônicos: Análise do comportamento planejado e da motivação de proteção - AMORIM, Lucas Silva de (2023)
The reason why people recycle or not has long been the focus of researchers and professionals seeking to understand and influence pro-environmental behaviors, thus becoming an integral part of academic life. In this context, as the transition to sustainability strengthens, recycling emerges as one of the fundamental concepts of sustainable behavior. To address the increase in electronic waste generation and its improper disposal, it is essential to examine the intentions and recycling behavior of these waste among consumers. The primary objective of this study is to investigate the factors that influence the recycling behavior of electronic waste. To achieve this purpose, a theoretical review covering the Theory of Planned Behavior, Protection Motivation Theory, and the theme of electronic waste was conducted. This research is classified as explanatory, descriptive, and quantitative, with a sample consisting of 305 individuals aged 18 and above. Data collection took place in the city of Maceió-AL, and the analysis was performed through structural equation modeling. The obtained results provide theoretical-empirical support for the effects of integrating the Theory of Planned Behavior and the Protection Motivation Theory through a unified theoretical model, applied in the context of electronic waste recycling. The main findings indicate that self-efficacy emerges as the primary predictor of recycling intention, while perceived behavioral control stands out as the most robust direct predictor of electronic waste recycling behavior. The results achieved in this study have significant implications for the consumer behavior field, especially in the electronic waste context. By deepening the understanding of motivations and determinants behind consumers' actions in this specific context, the study contributes to the theoretical and practical foundation in the field. Furthermore, the presented theoretical model can serve as a solid foundation for future research in the electronic waste recycling area.